Reciclagem química e eletroquímica de baterias exauridas de Ni-MH - Dixini, Pedro Vitor Morbach (2014)
Here in, new technology has been developed for recycling of metals from the cathodes and anodes of spent Ni-MH batteries. The cathodes recycling occurred through the electrodeposition of metals in galvanostatic conditions; also the mechanism of simultaneous electrodeposition of Ni, Co, Zn and Mn was studied in potentiodynamic, potentiostatic and galvanostatic conditions. Aluminium and vitreous carbon electrodes were used in electrodeposition. From cyclic voltammetry experiments at scan rates of 1, 5 and 10 mV.s-1, it was observed that the metals deposition occurs from the precipitation of hydroxides on the electrode surface, in which they are formed after alkalinization of the electrode/solution interface, due the hydrogen evolution reaction. From SEM analysis it was observed that in potentiostatic conditions, only the nucleation process takes place and there is no film growth, the nuclei were dissolved and analyzed by ICP OES, Ni, Co and Zn were detected as traces. In galvanostatic conditions the following current densities, were used, -20, -25 , -30 , -35 and -40 mA.cm-2 and the charge density was fixed in -50 C.cm-2. The greatest charge efficiency was observed for current densities of -25 and -40 mA.cm-2 in Al and -35 and -40 mA.cm-2 in the vitreous carbon. From the micrographs it was found that all electrodeposits presents a heterogeneous surface. XRD measurements identified Ni, Co, Ni(OH)2 and Mn3O4 at all electrodeposits. Using EIS, equivalent circuits were determined for all electrodeposits. All of them are of the form R1(R2Q)W, where R1 is the solution resistance across the pores and R2, Q and W are relative to the pores. The recycled films were analyzed by cyclic voltammetry in alkaline solution. A charge efficiency of 85 % was obtained, showing good suitability of the material as an electrochemical capacitor and electrochromic cells. The lanthanides presents at the anodes spent Ni-MH batteries were recovered as a mixture of Ln2(SO4)3, where Ln = La , Ce and Nd , and an efficiency of 99,9 % was found. The synthesis of (La.Nd)2O2S.CeO2 have been carried out by subjecting a mixture of La2(SO4)3, Ce2(SO4)3, and Nd2(SO4)3 to a heat treatment in a reducing atmosphere up to1000 °C. The (La.Nd)O2SO4.CeO2 compounds have been obtained after thermal treatment of (La.Nd)O2S.CeO2 in a synthetic air atmosphere. The oxysulfide/oxysulfate compounds have been subjected to thermal cycles, respectively, in synthetic air as well as in an N2-CO atmosphere. The thermogravimetric plot (TG) for (La.Nd)2O2S.CeO2 shows a mass gain of 14,98 % w/w in atemperature range of 300-550 °C, which is due to the oxidation of (La.Nd)2O2S.CeO2 to(La.Nd)2O2SO4CeO2, where 2 mol of O2 are added. Likewise, in the (La.Nd)2O2SO4CeO2 thermogravimetric plot, a mass loss of 17.16 % w/w is observed in the range of 500-750 °C. This loss of mass can be associated with output of 2 moles of O2 forming again the (La.Nd)2O2S.CeO2. The transformation of the (La.Nd)2.O2S.CeO2 to (La.Nd)2O2SO4CeO2 causes an increase in the macropores.